Thomas Eakins : The Heroism of Modern Life - Johns, Elizabeth, 1937- (Book collections on Project MUSE., 1983)
Why did Thomas Eakins, now considered the foremost American painter of the nineteenth century, make portraiture his main field in an era when other major artists disdained such a choice? With a rich discussion of the cultural and vocational context of the late nineteenth and early twentieth centuries, Elizabeth Johns answers this question.